The influence of the social network Instagram on tourist destination choice: Behavior of generations Y and Z - Đurović, Mihajlo; Vujović, Tanja; Perić, Goran; Behremen , Cesim (Hotel and Tourism Management, 2026)
Purpose – The objective of this study was to analyze the effect of various determinants included in the UTAUT2 model, with the addition of the construct of perceived trust, on the intention and actual behavior of Instagram users when choosing a tourist destination, with special reference to the behavior of two generational cohorts. Methodology – The study was conducted through an online survey on a sample of 531 respondents from Serbia. The questionnaire is constructed on validated scales and modified to the framework of using Instagram when choosing a tourist destination. Data analysis was performed in the programming language R, using the Pslpm package. Results – Across the entire sample, habit, hedonic motivation, social influence, and perceived trust impact behavioral intention, while habit, trust, and behavioral intention predict actual behavior. However, the findings showed that generational affiliation moderates the affiliation among enabling circumstances and authentic performance, with the consequence being positive and significant for Generation Z, but not for Generation Y. Implications – Theoretically, the discoveries confirm the status of integrating perceived trust into the UTAUT2 model and indicate a reduced role of technical factors in digitally literate populations. Practically, it is recommended to use formats and functionality of Instagram that are closer to younger users.